(untitled) (Research, Society and Development, 2020)
The aim of this study is to analyze the use of the tools of the Endomarketing in the supermarket sector of the municipality of Cruzeta / RN, from the point of view of the perception of the managers of the companies. The research is classified as descriptive and exploratory, with non-probabilistic sampling and information collection through a structured interview. The methods used for analysis are qualitative and quantitative, covering content and graph analysis and their respective results. Analyzing what actions are used in the effective endomarketing in companies, how these actions are organized and by whom, in addition to observing what benefits arise for employees with the practice of actions and if the desired return by managers is being obtained. With regard to the opinion of the respondents about the application of the endomarketing in the analyzed locality, it was perceived that it is a still new subject and that needs to be more argued and intensified in the organizations, besides being shown to be used of limited form due to the necessity of investment financial.